2013 Asilomar Conference on Signals, Systems and Computers 2013
DOI: 10.1109/acssc.2013.6810234
|View full text |Cite
|
Sign up to set email alerts
|

Compressed sensing for energy-efficient wireless telemonitoring: Challenges and opportunities

Abstract: Abstract-As a lossy compression framework, compressed sensing has drawn much attention in wireless telemonitoring of biosignals due to its ability to reduce energy consumption and make possible the design of low-power devices. However, the non-sparseness of biosignals presents a major challenge to compressed sensing. This study proposes and evaluates a spatio-temporal sparse Bayesian learning algorithm, which has the desired ability to recover such non-sparse biosignals. It exploits both temporal correlation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…If we tried to do this by exhaustively checking every possible subset of sources (assuming that at most N − 1 sources are active), then we would have to check O(M N−1 ) possibilities, as shown by equation (3).…”
Section: Measurement Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…If we tried to do this by exhaustively checking every possible subset of sources (assuming that at most N − 1 sources are active), then we would have to check O(M N−1 ) possibilities, as shown by equation (3).…”
Section: Measurement Modelsmentioning
confidence: 99%
“…In particular, compressed sensing methods have found use in wireless monitoring systems, where the reduced power draw by transmitting significantly less data is important due to the potential of significantly improving battery life [3]. However, it has been shown that in this case, a significant improvement may be achieved only if the sensing matrix is a binary matrix, and so not all methods are suitable.…”
Section: Introductionmentioning
confidence: 98%
“…It is worth pointing out that most CS algorithms may not be used for energy-efficient wireless telemonitoring especially ambulatory monitoring, due to several challenges [20]- [22].…”
Section: B Challenges In the Use Of Cs For Wireless Telemonitoringmentioning
confidence: 99%
“…Thus, the collected physiological signals are inevitably contaminated by strong artifacts caused by muscle movement and electrode motion. As a result, even a sparse signal can become nonsparse in the time domain and also non-sparse in transformed domains [20]. The non-sparsity seriously degrades CS algorithms' performance, resulting in their failure [6].…”
Section: B Challenges In the Use Of Cs For Wireless Telemonitoringmentioning
confidence: 99%
See 1 more Smart Citation